Cluster-adaptive two-phase coding multi-channel MAC protocol (CA-TPCMMP) for MANETs - Zhang, Lili (2011)
This paper introduces a novel joint clustering and multi-channel medium access control (MAC) protocol for mobile ad hoc networks (MANETs) based on a scalable two-phase coding scheme, where the first-phase code is used for differentiating the clusters and the second-phase code is employed to distinguish the nodes in a specific cluster. It mitigates the hidden terminal problem (HTP) during data transmission and efficiently incorporates the procedure of code assignment with adaptive clustering. We also introduce the connection detection and confliction resolution mechanisms for the allocation of the first-phase code in the control channel. Simulation results show that substantial improvement in terms of control overhead can be achieved by the proposed protocol over the traditional distributed code division multiple access (CDMA) based multi-channel MAC algorithms with clustering or without clustering.